BELAJAR BERBASIS e-EDUCATION BAGI LANSIA - Prasetyo, Eko Budi (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Area like social, political, education, religion, artistic, research of knowledge and technology development have indicated for us that a lot of old figureachievement capable to primaly. Education have ought ti give the attention to phenomenon like that, because principal relevant with a few like: Education for all and Life long education.All society segment require to be motivated will taking benefit of information technology to learn, olso for old aging society group. Thereby e-Education able to form the society learning.